Extraordinary endangered animals - Silhol, Sandrine; Doucedame, Marie; Guerive, Gaelle (Abrams Books for Young Readers, 2011)
Provides information about natural habitats, relationships with people, and threats to survival for thirty-five endangered animals from around the world and explores waysthat individuals can help protect these animals and all of the earth's inhabitants